The Effect of Financial Performance, Environmental Performance, and Carbon Emission Disclosure on Firm Value: A Cognitive Learning Preferences Perspective - Sari, Intan; Azis, Mohammad Taufik; Djajuli, Mohamad (Journal Corner of Education, Linguistics, and Literature, 2025)
This study examined the effect of financial performance, environmental performance, and carbon emission disclosure on firm value. The research population consists of energy and basic materials sector companies listed on the Indonesian Stock Exchange (IDX) during the period 2021–2023, with a final sample of 33 companies. Data were obtained from financial reports, sustainability reports accessed via IDX and company websites, as well as PROPER KLHK documentation. The study employs a quantitative approach with panel data regression analysis. The findings reveal that financial performance has a significant positive effect on firm value, whereas environmental performance and carbon emission disclosure do not demonstrate significant effects. Beyond its empirical contribution, this study also offers implications for business education, particularly in aligning sustainability and financial analysis with cognitive learning preferences. By integrating these findings into diverse instructional modalities, educators can foster a deeper understanding of the interplay between financial performance, environmental responsibility, and corporate value among future professionals.